A multiparametric and orthogonal approach indicates low toxicity for zein nanoparticles in a repellent formulation - Almeida, Tuanny Leite; Moreira, Aline Francisca; de Oliveira, Jhones Luiz [UNESP]; Rogerio, Carolina Barbara [UNESP]; Kiihl, Samara Flamini; Fraceto, Leonardo Fernandes [UNESP]; de Jesus, Marcelo Bispo (Elsevier, 2024)
The incidence of viruses such as Zika, Dengue, and Chikungunya affects human health worldwide, and insect repellents are recommended for individual protection. Formulations incorporating nanotechnology should be carefully assessed for toxicity, particularly regarding the security levels established for human health and the environment. This study evaluates the cytotoxicity of a repellent formulation containing zein nanoparticles (NP) loading geraniol (Ger) and icaridin (Ica) in three cell lines: NIH/3T3, HaCaT, and SIRC. To address formulation hazards, IC50 values were determined by MTT and Calcein-AM assays. In both NIH/3T3 and HaCaT, the IC50 values for NP + Ger + Ica formulation were around 0.2%. For risk assessment, cell viability was also determined after a single exposure and repeated exposure to the formulation. No evidence of cytotoxicity was observed for NP + Ger + Ica formulation-treated cells. The risk assessment for eye damage revealed cytotoxicity in SIRC cells when exposed to a 5% concentration, which may be attributed to ocular geraniol toxicity, because zein nanoparticles alone did not exhibit any signs of toxicity. Cell internalization indicated low uptake in NIH/3T3 and HaCaT cells. Phenotypic profiling resulted in similar phenotypes for untreated cells and cells exposed to NP + Ger + Ica formulation. The toxicological profile outlined by the multiparametric and orthogonal approach suggests that the NP + Ger + Ica formulation poses no significant risk to the topical application under the tested conditions. Adopting an orthogonal approach brings robustness to our findings.
Keywords: Cytotoxicity; Orthogonal approaches; Repellents; Risk assessment; Zein nanoparticles